Dietary meat mutagens intake and cancer risk: A systematic review and meta-analysis - Reng, Qie; Zhu, Ling Ling; Feng, Li; Li, Yong Jie; Zhu, Yan Xing; Wang, Ting Ting; Jiang, Feng (Frontiers in Nutrition, 2022)
Background: Clinical and preclinical studies suggested that certain mutagens occurring as a reaction of creatine, amino acids, and sugar during the high temperature of cooking meat are involved in the pathogenesis of human cancer. Here we conducted a systematic review and meta-analysis to examine whether meat mutagens (PhIP, MeIQx, DiMeIQx, total HCA and, B(a)P)) present a risk factor for human cancer. Methods: We searched the following databases for relevant articles published from inception to 10 Oct 2021 with no language restrictions: Pubmed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), Baidu Academic, Zhejiang Digital Library. Two independent researchers screened all titles and obtained eligible texts for further screening. Independent data extraction was conducted, and meta-analysis was carried out using random-effects models to calculate the risk ratio of the meat mutagens exposure. Results: A total of 1786410 participants and 70653 cancer cases were identified. Among these, there were 12 different types of cancer at various sites, i.e., breast, bladder, colorectal, colon, rectum, prostate, lung, Non-Hodgkin lymphoma, kidney, gastric, esophagus, pancreatic, hepatocellular carcinoma. Cancer risk was significantly increased by intake of PhIP (OR= 1.13;95%CI 1.07-1.21 ; p<0.001), MeIQx (OR= 1.14; 95% CI: 1.07-1.21; p<0.001), DiMeIQx (OR= 1.07; 95% CI: 1.01-1.13; p= 0.013), total HCA (OR=1.20; 95%CI: 1.03-1.38; p= 0.016), and cancer risk was not significantly increased by intake of B(a)P (OR= 1.04; 95% CI: 0.98-1.10; p= 0.206). Conclusions: Meat mutagens of PhIP, MeIQx, DiMeIQx, and total HCA have a positive association with the risk of cancer.